Visual loss in giant cell arteritis 3 weeks after steroid initiation. Issue 3 (6th March 2019) - Le Goueff, Anouk; Peters, James; Willcocks, Lisa; Jayne, David
Abstract : Giant cell arteritis (GCA) is the most common vasculitis in adults and blindness is a common complication if left untreated. Oral glucocorticoids are the mainstay of treatment and if started promptly, loss of vision can usually be prevented. We present the case of a 77-year-old man who developed irreversible bilateral blindness after a confirmed diagnosis of GCA and oral steroid treatment. The roles of diagnostic delay, steroid dosing, significance of visual symptoms at diagnosis and after commencing oral glucocorticoids, and interpretation of ophthalmological signs are reviewed.